Edukasi Teknik Pernapasan Untuk Mengurangi Nyeri Pada Ibu Bersalin Kala I - Norma Safitri; Abdillah Abdillah; Karnelly Karnelly; Cakrawati R; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
The labor process is a physiological event that is often accompanied by pain due to uterine contractions. Uncontrolled pain can cause fatigue, anxiety, and even slow down the progress of labor. One effective non-pharmacological method for reducing pain is breathing techniques. This community service activity aims to increase the knowledge and skills of pregnant women regarding proper breathing techniques when facing the first stage of labor. The activity was carried out at Puskesmas X, targeting 25 pregnant women in their third trimester. The activity methods included education, demonstration, and hands-on practice. The results of the activity showed an increase in participants' understanding of breathing techniques from 60% before education to 92% after education. Participants also reported an increase in their confidence in facing labor. This activity is expected to become a sustainable program in efforts to support safe and comfortable labor for mothers.